IMPLEMENTASI PENDIDIKAN KARAKTER NILAI RELIGIUS PADA MATA PELAJARAN SEJARAH KELAS X IIS DI SMA MUHAMMADIYAH 1 PONTIANAK - Abdullah, Imam; Firmansyah, Andang; Firmansyah, Haris (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
Thisresearch tries to analyze the implementation of religious character education in history subjects among Grade X IIS students at SMA Muhammadiyah 1 Pontianak. Religious character education is essential in shaping a generation that excels not only in knowledge and skills but also in moral integrity. The study takes a descriptive qualitative method, gathering data through observation, interviews, and recording. The findings reveal that history teachers have effectively designed and implemented learning activities based on religious values using lesson plans (RPP), while also cultivating religious habits among students, such as reciting the Qur"™an (tadarus), praying together, and demonstrating respectful behavior in the classroom. The school also supports character development through various programs rooted in Islamic values. However, challenges remain in implementing religious character education, particularly due to the limited instructional time for history subjects, which is only two hours per week. This constraint reduces the teacher's ability to consistently monitor students' religious behavior. As a solution, the history teacher and the school have developed a historical excursion program to visit historical sites, including places of worship, to instill religious values in a contextual manner. Overall, implementing religious character education at SMA Muhammadiyah 1 Pontianak is progressing well but still requires strong collaboration among teachers, the school, students, and parents for optimal outcomes.